Investigating digital library success using the DeLone and McLean information system success 2.0: The analysis of common factor based structural equation modeling - Afthanorhan, A.; Foziah, H.; Majid, N.A. (2020)
In many years, libraries from government universities spent a vast amount of investment to subscribe to various digital resources such as online reputable publishers, journals, online databases, books, monographs, and other resources for information storage. However, prior studies reported that the utilization of digital library is remain lacking though online libraries were able successfully find the necessary information. This is confirmatory study to model and investigating the determinant of user satisfaction of a digital library system. A research model was adopted from an existing model as Delone and McLean Information system success .. Data were collected using cluster sampling technique. A total of usable questionnaires were used for empirical study purpose. The results showed that Information Quality is the strongest effect in contributing the user satisfaction followed by the quality factors (System Quality and Service Quality). In additions, the Preacher & Hayes approach was used for testing the indirect effect. From this approach, partial mediation was occurred in all effects. Briefly, the behavioural intentions are greatly influenced by the quality factors and Information System.